2008
DOI: 10.1159/000195698
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of <i>p</i>16<sup>INK4A</sup> and Mitotic Arrest Defective Protein 2 (<i>MAD</i>2) Genes in Gastric Marginal-Zone B-Cell Lymphomas

Abstract: Background: Products of cyclin-dependent kinase inhibitor p16INK4Aand mitotic arrest defective protein 2 (MAD2) genesare key regulator proteins at the G1 restriction point and mitotic checkpoint of the cell cycle. The objective of this study was to investigate the role of promoter methylation of p16INK4A and MAD2 genes in gastric marginal-zone B-cell lymphoma (MZBCL). Materials and Methods: Gastric biopsies from 40 patients were analyzed by methylation-specific polymerase chain reaction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
0
9
1
Order By: Relevance
“…Previous studies have shown that P16 is underexpressed more frequently in gastric MALT than in other lymphoma types [20,21]. This has been shown to primarily relate to p16 promoter hypermethylation in non-transformed MALTs [20,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that P16 is underexpressed more frequently in gastric MALT than in other lymphoma types [20,21]. This has been shown to primarily relate to p16 promoter hypermethylation in non-transformed MALTs [20,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The silenced tumor suppressor genes further drive these cells to undergo malignant transformations through the abnormal promotion of cell proliferation and cell cycle alterations [68,69,70]. For gastric lymphoma, several studies have reported that the methylation of p16 INK4A , an inhibitor of cyclin-dependent kinases, may be associated with the development of gastric MALT lymphomas [71,72,73]. Kim et al reported that p16 hypermethylation was detected in seven (58%) of 12 patients with HP-dependent gastric MALT lymphoma [71].…”
Section: Epigenetic Changes and Genetic Changes Are Involved In Thmentioning
confidence: 99%
“…[56][57][58] Park et al demonstrated that p16 INK4A methylation occurred more frequently in t(11;18)(q21;q21)-negative gastric MALT lymphoma, whereas methylation of the MAD2 gene was associated with BCL10 expression. 58 In a recent study on the relationship between the CpG-island-methylator phenotype (CIMP) and gastric lymphoma, Kondo et al showed that H pylori-positive gastric lymphoma was associated with a significantly higher incidence of CIMP (93%, 27/29) than that of H pylori-negative gastric lymphoma (42%, 5/12; P Ͻ .001). 59 Aberrant CpG methylation of certain genes, such as p16, MGMT, and MINT31, was associated with H pylori infection.…”
Section: Direct Effects Of H Pylori On B-cell Proliferation In Gastrimentioning
confidence: 99%